Estudio de factibilidad para la implementación de un proyecto turístico en el sector Puerto Alto del Cantón Bolívar - Quijije García, Evelyn Juleidy (2022)
The general objective of this research was to conduct a feasibility study for the creation of a tourist center in the Puerto Alto sector in Bolivar Canton, Manabi province, for its development it was necessary to apply a descriptive and field study, requiring the methodological application of four phases, which began with a situational diagnosis of the area planned for its implementation through data collection instruments such as interviews, serving as a basis for analyzing the macro environment using tools such as the Pestel and the micro environment, through Porter's 5 forces and the SWOT matrix; EFE; EFI, then, to know the potential demand of the tourism sector, a market study was applied, and consequently through phase three a technical study was carried out, while in stage four an economic-financial analysis was applied. The resulting data made it possible to establish market, technical and economic feasibility, since there was a high level of acceptance by the surveyed population, the area complies with the appropriate environmental conditions, and the calculation of the financial indicators reflects the profitability of the investment with a recovery period of four years, which leads to the conclusion that the project is feasible.